1985
DOI: 10.1038/clpt.1985.195
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and beta-blocking effects of timolol in poor and extensive metabolizers of debrisoquin

Abstract: We studied the pharmacokinetics and beta-blocking effects of a single, oral 20 mg dose of timolol in six poor metabolizers (PMs) and six extensive metabolizers (EMs) of debrisoquin. The plasma timolol concentration was significantly higher in PMs than in EMs. There was a fourfold difference in mean AUC (1590 +/- 1133 vs. 394 +/- 239 ng X hr/ml; P less than 0.01) and a twofold difference in mean t1/2 (7.5 +/- 3 vs. 3.7 +/- 1.7 hours; P less than 0.01), reflecting differences in oral clearance (13.1 +/- 7.8 vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…The higher plasma timolol concentrations observed in PMs confirm earlier findings of Lewis et al (1985) and McGourty et al (1985a). However, the considerable overlap between phenotypic groups suggests that maximum separation may not be achieved at 2 h after dosing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The higher plasma timolol concentrations observed in PMs confirm earlier findings of Lewis et al (1985) and McGourty et al (1985a). However, the considerable overlap between phenotypic groups suggests that maximum separation may not be achieved at 2 h after dosing.…”
Section: Discussionsupporting
confidence: 79%
“…Two independent panel studies have shown that the pharmacokinetics and 1-adrenoceptor antagonist activity of timolol are related to debrisoquine oxidation phenotype (Lewis et al, 1985;McGourty et al, 1985a). The mean areas under the plasma drug concentration time-curve were two to four times higher in poor metabolisers (PMs) than in extensive metabolisers (EMs) of debrisoquine.…”
Section: Introductionmentioning
confidence: 99%
“…Timolol is a nonselective ␤-blocker that is metabolized largely by CYP2D6. PMs have a 2-to 4-fold higher mean AUC and increased and prolonged ␤-blockade after oral administration (Lewis et al, 1985;McGourty et al, 1985a). ␤-Blockade can occur with very low plasma concentrations of timolol , and ocular administration has been associated with systemic side effects (van der Zanden et al, 2001).…”
Section: Antipsychoticsmentioning
confidence: 99%
“…For example, timolol is metabolized by cytochrome P40 2D6 (CYP2D6). Polymorphisms in this gene are associated with reduced efficacy of oral timolol in patients with systemic hypertension (McGourty et al, 1985). In a series of 19 OAG patients and 18 volunteers, poor metabolizers of CYP2D6 demonstrated higher systemic concentrations of ophthalmic timolol, suggesting a potential safety concern in these patients (Nieminen et al, 2005).…”
Section: β-Adrenergic Antagonistsmentioning
confidence: 99%